Avoiding word accent errors, but how – on the automation of correct accent position in German among Polish students of German studies - Żytyńska, Małgorzata (Acta Universitatis Lodziensis. Folia Germanica, 2023)
The article deals with the recurrent incorrect accent position in the German words articulated by Polish learners, whether when reading aloud or speaking. This seems all the more serious because incorrect word accent (as well as incorrect sentence accentuation) can contribute to communication problems or even misunderstandings. The main problem here is the frequency of the errors, which are always corrected, but without success. The article is meant as a postulate to work out efficient automation methods.